Microstructure and mechanical properties of in situ TiB2•TiAl3/2024Al composite subjected to multidirectional forging - Qiang Chen; Haoyu Geng; Hongming Zhang; Xin Li; Gang Chen (Journal of Materials Research and Technology, 2022)
The TiB2•TiAl3/2024Al composite fabricated by in situ reaction method was subjected to multidirectional forging (MDF) and the effects of temperature and pass number of MDF on the microstructure and mechanical properties of the composite were investigated. By increasing the MDF temperature (from 350 to 500 °C) or increasing the number of MDF passes (from 1 to 4 passes), the fraction of high-angle grain boundaries (HAGBs) increased, and the average grain size of the Al matrix decreased. The tensile strength and elongation of the composite improved with increasing MDF temperature and pass number. After 4 MDF passes at 450 °C, the average grain size of the composite decreased from 45.00 to 3.08 μm, and the tensile strength and elongation increased by 12.78% and 282.46%, respectively. During the MDF process, a great number of TiAl3 particles fractured, and the size of TiAl3 decreased. Meanwhile, the agglomeration of TiB2 particles reduced, and the clustering of TiB2 particles tended to elongate and directional alignment. Both discontinuous dynamic recrystallization (DDRX) and continuous dynamic recrystallization (CDRX) occurred during the MDF process, which had a close relationship with the size and distribution of TiB2 and TiAl3 particles. The improvement of strength caused by MDF processing for the studied composite was quantitatively analyzed by models of the strengthening mechanism. The calculated results indicate that the load transfer effect and thermal expansion mismatch effect may partially counteract the effects of grain refinement on the enhancement of strength.